Freeing Charles : The Struggle to Free a Slave on the Eve of the Civil War - Christianson, Scott (Book collections on Project MUSE., 2010)
Freeing Charles recounts the life and epic rescue of captured fugitive slave Charles Nalle of Culpeper, Virginia, who was forcibly liberated by Harriet Tubman and others in Troy, New York, on April 27, 1860. Scott Christianson follows Nalle from his enslavement by the Hansborough family in Virginia through his escape by the Underground Railroad and his experiences in the North on the eve of the Civil War. This engaging narrative represents the first in-depth historical study of this crucial incident, one of the fiercest anti-slavery riots after Harpers Ferry. Christianson also presents a richly detailed look at slavery culture in antebellum Virginia and probes the deepest political and psychological aspects of this epic tale. His account underscores fundamental questions about racial inequality, the rule of law, civil disobedience, and violent resistance to slavery in the antebellum North and South.